2019
DOI: 10.1177/1099636219857200
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration and aspect ratio effects on the long-term creep of carbon nanotubes/fiber/polymer composite cylindrical shells

Abstract: The present study is an attempt to trace the influences of agglomeration, uniform dispersion, and aspect ratio of carbon nanotubes on long-term creep strain and stress in carbon nanotubes/fiber/polymer composite cylindrical shells. The thin-walled cylindrical vessel is subjected to an internal pressure. For this purpose, the effect of the carbon nanotubes agglomeration and aspect ratio on the elastic properties of carbon nanotube-reinforced composites were investigated, by means of the Halpin–Tsai and Eshelby–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This could be due to the fracture of agglomerates during the sample preparation process or to pre-existing internal flaws [ 46 ]. Defining the aspect ratio of the agglomerate as the ratio of their vertical length i.e., the length parallel to the loading direction, to the agglomerate’s horizontal length [ 47 ], it can be seen from Figure 8 that the apparent correlation between the shape, orientation, and alignment of the agglomerates was causing the crack initiation. We observed from the SEM micrographs that the silica agglomerates of aspect ratio greater than one (i.e., the longest length is oriented along the loading direction) were mostly fractured into halves.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to the fracture of agglomerates during the sample preparation process or to pre-existing internal flaws [ 46 ]. Defining the aspect ratio of the agglomerate as the ratio of their vertical length i.e., the length parallel to the loading direction, to the agglomerate’s horizontal length [ 47 ], it can be seen from Figure 8 that the apparent correlation between the shape, orientation, and alignment of the agglomerates was causing the crack initiation. We observed from the SEM micrographs that the silica agglomerates of aspect ratio greater than one (i.e., the longest length is oriented along the loading direction) were mostly fractured into halves.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that, as also discussed by Ghasami et al 33,34 uniform and homogeneous dispersion of CNTs in the matrix is extremely important for the improvement of all properties of composite materials. For this purpose, SEM analysis was conducted on the fracture surfaces of the flexural three-point bending specimens.…”
Section: Distribution Of Cnts In Epoxy Matrixmentioning
confidence: 87%
“…When η > μ, the heterogeneity of the CNTs distribution grows with the increase of η. 25,26 To analyze the agglomeration effects, primarily the effective elastic stiffness of the clusters and the matrix should be estimated. Among different micromechanical methods for estimating the elastic properties of the clusters and the matrix, the MT method is used in this research.…”
Section: Analytical Formulationmentioning
confidence: 99%
“…Employing the GDQM, they illustrated that agglomeration parameters μ and η have a significant effect on the natural frequencies, but can't alter the wave number. Hosseinpour and Ghasemi 25 investigated the effects of CNTs agglomeration on long-term creep strain and stress in composite cylindrical shells and showed that CNTs agglomeration increases the creep strain. The influences of CNTs agglomeration on the vibration of multi-phase cylindrical shells have been studied by Ghasemi et al 26 A method for investigating the effect of aggregation on CNTs composites developed using micromechanics model predicted the elastic properties of reinforced polymers with the agglomeration of fillers.…”
Section: Introductionmentioning
confidence: 99%